Inkjet and inkjet-based 3D printing: connecting fluid properties and printing performance. Issue 3 (18th April 2017) - Guo, Yang; Patanwala, Huseini S.; Bognet, Brice; Ma, Anson W.K.
Abstract : Purpose: This paper aims to summarize the latest developments both in terms of theoretical understanding and experimental techniques related to inkjet fluids. The purpose is to provide practitioners a self-contained review of how the performance of inkjet and inkjet-based three-dimensional (3D) printing is fundamentally influenced by the properties of inkjet fluids. Design/methodology/approach: This paper is written for practitioners who may not be familiar with the underlying physics of inkjet printing. The paper thus begins with a brief review of basic concepts in inkjet fluid characterization and the relevant dimensionless groups. Then, how drop impact and contact angle affect the footprint and resolution of inkjet printing is reviewed, especially onto powder and fabrics that are relevant to 3D printing and flexible electronics applications. A future outlook is given at the end of this review paper. Findings: The jettability of Newtonian fluids is well-studied and has been generalized using a dimensionless Ohnesorge number. However, the inclusion of various functional materials may modify the ink fluid properties, leading to non-Newtonian behavior, such as shear thinning and elasticity. This paper discusses the current understanding of common inkjet fluids, such as particle suspensions, shear-thinning fluids and viscoelastic fluids. Originality/value: A number of excellent review papers on the applications of inkjet and inkjet-based 3D printing already exist. This paper focuses on highlighting the current scientific understanding and possible future directions.